Effects of Caralluma russeliana stem extract on some physiological parameters in streptozotocin-induced diabetic male rats - Zari TA (Dove Medical Press, 2018)
Talal A Zari, Mesfer A Al-Thebaiti Department of Biological Sciences, Faculty of Science, King Abdulaziz University, Jeddah, Saudi Arabia Purpose: The aim of this study was to investigate the effects of Caralluma russeliana stem extract on some physiological parameters in streptozotocin induced diabetes in male Wistar rats after 8 weeks. Materials and methods: The experimental rats were randomly assigned into four groups. Rats of group 1 were normal controls. Rats of group 2 were diabetic controls. Rats of group 3 were diabetic rats treated with C. russeliana stem extract. Rats of group 4 were non-diabetic rats, subjected to C. russeliana stem extract. Results: The lowest body weight gain was noticed in diabetic rats of group 2. Serum glucose, triglycerides, cholesterol, low-density lipoprotein cholesterol, very low-density lipoprotein cholesterol, alanine aminotransferase, aspartate aminotransferase, ALP, total bilirubin, creatinine, blood urea nitrogen (BUN) and uric acid levels were significantly elevated in diabetic rats of group 2; however, total serum protein, albumin and high-density lipoprotein cholesterol were significantly reduced in diabetic rats of group 2. Conclusion: Treatments with C. russeliana stem extract in diabetic rats revealed notable diminishing and protecting effects of physiological modifications. Therefore, this study revealed the significance of using C. russeliana stem extract as a promising remedial agent to treat diabetes and its complications. Keywords: Caralluma russeliana, diabetes, streptozotocin, weight loss, glucose, lipids, liver enzymes, kidney function, rats